2023
DOI: 10.3389/fninf.2023.1211188
|View full text |Cite
|
Sign up to set email alerts
|

Microglial morphometric analysis: so many options, so little consistency

Jack Reddaway,
Peter Eulalio Richardson,
Ryan J. Bevan
et al.

Abstract: Quantification of microglial activation through morphometric analysis has long been a staple of the neuroimmunologist’s toolkit. Microglial morphological phenomics can be conducted through either manual classification or constructing a digital skeleton and extracting morphometric data from it. Multiple open-access and paid software packages are available to generate these skeletons via semi-automated and/or fully automated methods with varying degrees of accuracy. Despite advancements in methods to generate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 174 publications
1
13
0
Order By: Relevance
“…pathogens, debris, injury), microglia retract and exhibit large soma size and thickening, entering an ‘ameboid’ state. Evidence has accumulated that microglial morphology may be more complex than this dichotomy between ‘surveying’ and ‘ameboid’ microglia (Vidal-Itriago et al, 2022; Leyh et al, 2021; Reddaway et al, 2023). Our chronic negative engram activation may induce an ‘insult’ on the brain, as evidenced by an increase in Iba1 expression and hyper-ramified morphology, indicating a complex change in microglial phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pathogens, debris, injury), microglia retract and exhibit large soma size and thickening, entering an ‘ameboid’ state. Evidence has accumulated that microglial morphology may be more complex than this dichotomy between ‘surveying’ and ‘ameboid’ microglia (Vidal-Itriago et al, 2022; Leyh et al, 2021; Reddaway et al, 2023). Our chronic negative engram activation may induce an ‘insult’ on the brain, as evidenced by an increase in Iba1 expression and hyper-ramified morphology, indicating a complex change in microglial phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…pathogens, debris, injury), microglia retract and exhibit large soma size and thickening, entering an 'ameboid' state. Evidence has accumulated that microglial morphology may be more complex than this dichotomy between 'surveying' and 'ameboid' microglia (Vidal-Itriago et al, 2022;Leyh et al, 2021;Reddaway et al, 2023).…”
Section: Chronic Stimulation Of Engrams Alter Behavior and Cellular R...mentioning
confidence: 99%
“…Results using morphOMICS indicated that the morphology of microglia was brain region and sex specific, as discussed above [ 110 ]. For a comprehensive review of microglial morphology methods, please refer to [ 113 ].…”
Section: Methods To Measure Microglial Morphologymentioning
confidence: 99%
“…(Dubbelaar et al, 2018;Paolicelli et al, 2022) In line with these efforts, there have been many recently published tools that classify and analyze microglia morphological subpopulations in an automated and high-throughput manner. (Clarke et al, 2021;Colombo et al, 2022;Hrj et al, 2023;Leyh et al, 2021;Reddaway et al, 2023;Salamanca et al, 2019;York et al, 2018) Using our toolset, MicrogliaMorphology and MicrogliaMorphologyR, we take a datainformed approach to characterize different populations of microglia morphologies and to available to download and all relevant materials including input images, data, and supporting code used in this study will be available on the OSF website when the paper is published.…”
Section: Microgliamorphology and Microgliamorphologyr A High-throughp...mentioning
confidence: 99%